Preparing for the Future: Will Our University Graduates be Scientifically Literate? - Patterson, Judith (Geoscience Canada, 1993)
Abstract In today's technological society, it is be-coming increasingly necessary to havean understanding of basic scientificfacts and processes in order to makeinformed choices, both in one's person-al activities and on issues of public pol-icy. People in developed nations rou-tinely make decisions on issues thathave a scientific, technological and/or environmental component, eitherthrough their personal activities orthrough their work. Consequently, alevel of knowledge of basic scientificfacts and processes is an essential in-gredient for informed decision making.Recent surveys of adults in the United States, United Kingdom, andCanada have detected some indica-tions of fundamental scientific illiteracyin the adult populations. Positions ofresponsibility that entail policy develop-ment and decision making are oftenheld by university graduates. Therefore,a survey of undergraduate students atErindale College of the University ofToronto was undertaken to determinethe levels of knowledge of scientificprinciples and processes in this seg-ment of the population. More than 1000 student responses tothe survey were recorded. The ques-tions pertained to basic scientific princi-ples and processes (planetary motion,pasteurization, lasers, geologic time,changing seasons, atomic structure,photosynthesis, acidic fluids, plate tec-tonics, evolution and medicine), and en-vironmental issues (tropical forests,stratospheric ozone, greenhouse ef-fect, and acid rain). The group as awhole scored 66% correct. Three vari-ables producing main effects in level ofperformance on the test were gender,year and discipline. Males consistentlyscored higher than females at equiv-alent levels of education, students in thelife and physical sciences did betterthan those in the humanities or socialsciences, and test performance im-proved with level of education. Theeffect of the location of high school thestudent had attended was not signifi-cant. The highest scores on the testwere achieved by males in the fourthyear of the physical sciences (88% cor-rect). The questions with the lowest cor-rect response rate were those pertain-ing to geology (49% correct).